Differences and Similarities Between English and Uzbek Cases - Xudoyarova Dildora Najmiddinovna; Khalikova Dildora Yadullayevna; Ismailova Guzal Fayzullayevna; Siddiqov G’iyos Yusufovich (International Journal on Orange Technologies, 2021)
In this scientific article the similarities of the agreements in English and Uzbek also point out the differences between them. The article provides a number of examples of the importance of agreements in Uzbek and English. it is highly proved that by this article some problems, complexities of grammar will be to some extent solved. From this article not only ESL student manage to use but also native speakers of English can utilize in acquiring Uzbek in the future